Low-loss tunable 1D ITO-slot photonic crystal nanobeam cavity. (17th April 2018) - Amin, Rubab; Tahersima, Mohammad H; Ma, Zhizhen; Suer, Can; Liu, Ke; Dalir, Hamed; Sorger, Volker J
Abstract: Tunable optical material properties enable novel applications in both versatile metamaterials and photonic components including optical sources and modulators. Transparent conductive oxides (TCOs) are able to highly tune their optical properties with applied bias via altering their free carrier concentration and hence plasma dispersion. The TCO material indium tin oxide (ITO) exhibits unity-strong index change and epsilon-near-zero behavior. However, with such tuning the corresponding high optical losses, originating from the fundamental Kramers–Kronig relations, result in low cavity finesse. However, achieving efficient tuning in ITO-cavities without using light–matter interaction enhancement techniques such as polaritonic modes, which are inherently lossy, is a challenge. Here we discuss a novel one-dimensional photonic crystal nanobeam cavity to deliver a cavity system offering a wide range of resonance tuning range, while preserving physical compact footprints. We show that a vertical silicon-slot waveguide incorporating an actively gated-ITO layer delivers ∼3.4 nm of tuning. By deploying distributed feedback, we are able to keep the Q -factor moderately high with tuning. Combining this with the sub-diffraction limited mode volume (0.1 ( λ /2 n ) 3 ) from the photonic (non-plasmonic) slot waveguide, facilitates a high Purcell factor exceeding 1000. This strong light–matter-interaction shows that reducing the mode volume of a cavity outweighs reducing the losses in diffraction limited modal cavities such as those from bulk Si3 N4 . These tunable cavities enable future modulators and optical sources such as tunable lasers.